TRADISI PAGA RUMAH DALAM PERNIKAHAN DI TERATAK PANAS: PERSPEKTIF ‘URF - insani, silvisri; Insani, Silvi Sri; Putri, Helvia; Putri, Weldra Ayu; Elvionita, Elsa (Usroh, 2024)
The Paga Rumah tradition in Teratak Panas weddings is one of the local cultural heritages that aims to maintain family honor and strengthen social relations. The Paga Rumah tradition aims to avoid bad things, such as hampering problems or witchcraft from other people, as well as ensuring that household appliances, such as plates and glasses, do not break. In Islamic law, local traditions that do not contradict sharia can be accepted as ‘urf. This research aims to examine the implementation of the Paga Rumah tradition in Teratak Panas and review the perspective of Islamic law (‘urf) on the tradition. The method used in this research is qualitative with a descriptive approach. The informants involved in this research are the people who are directly involved in the practice as well as traditional leaders in Teratak Panas. The results show that the process of implementing the Paga Rumah tradition involves the preparation of equipment by the shaman, reading prayers, and watering water containing a mixture of leaves around the house. The Paga Rumah tradition in Teratak Panas through the 'urf perspective can be guided by the extent to which the practices carried out are in accordance with sharia principles. If this tradition is carried out by paying attention to sharia principles and avoiding all forms of practices that are contrary to Islam, then the Paga Rumah tradition can be considered as 'urf shahih, which means a custom that is accepted and respected in society. However, if there are elements that contradict these principles, then this tradition is considered as 'urf fasid and must be reviewed to ensure its compatibility with Islamic teachings.